Prognostic prediction of male recipients selected for liver transplantation: With special attention to neutrophil to lymphocyte ratio. Issue 9 (18th January 2016) - Wang, Wei; Ye, Yufu; Wang, Ting; Zhang, Feng; Geng, Lei; Yu, Jun; Zhou, Lin; Yan, Sheng; Zheng, Shusen
Abstract : Aim: Neutrophil to lymphocyte ratio (NLR) is an inflammatory biomarker that has a close relationship with tumor progression and metastasis. In this study, we aimed to investigate the role of NLR in the prognosis of male candidates with hepatocellular carcinoma (HCC) undergoing liver transplantation (LT). Methods: We analyzed the clinical data of 248 male HCC candidates who underwent LT in our Liver Transplantation Center between 2002 and 2012. All risk factors were analyzed by univariate and multivariate Cox analysis and survival rates were calculated by Kaplan–Meier log–rank test. Results: NLR was proved to be an independent risk factor affecting overall survival (OS) ( P  < 0.001) and tumor‐free survival (TFS) ( P  = 0.003) of male candidates with HCC following LT. Additionally, our study showed that elevated NLR (>4) was associated with early tumor recurrence by Kaplan–Meier analysis. Furthermore, we established Model_OS and Model_TFS to predict prognosis based on multivariate Cox analysis. Our study showed that male candidates with HCC who exceeded the Milan criteria but within Model_OS could achieve similar OS as those within the Milan criteria ( P  = 0.220). Similarly, male patients who exceeded the Milan criteria but within Model_TFS could achieve similar TFS as those within the Milan criteria ( P  = 0.197). Conclusion: Proper inflammatory response may effectively reduce tumor recurrence after LT. Elevated NLR (>4) within a certain range is associated with early tumor recurrence. NLR‐based models are efficient and safe for prognostic prediction among male candidates with HCC for LT.